Water source of artificial plants in the northeastern margin of Tengger Desert based on hydrogen and oxygen stable isotopes - Zhao, Zhenyu; Tang, Guodong; Li, Jinrong; Wu, Meng; Zhang, Lei (Frontiers in Plant Science, 2025)
Understanding water sources and utilization strategies is essential for the water use patterns of vegetation restoration species and achieving sustainable vegetation restoration. The water use strategies of Corethrodendron scoparium and Calligonum mongolicum were studied in the afforestation area on the northeastern edge of the Tengger Desert, to provide scientific guidance for regional vegetation restoration and stand structure adjustment. We utilize hydrogen and oxygen isotope techniques and the MixSIAR model to calculate the contribution rates of these two plant species to various potential water sources from June to October. By calculating the PS index, we determined the competitive relationship of C. scoparium and C. mongolicum towards different water sources. The results showed that the soil moisture content in the 0-80 cm soil layer changed significantly due to rainfall and evaporation, but stabilized with increasing depth. Shallow soil water shows enriched stable isotope composition, while the isotope of groundwater is relatively stable, and the isotope of precipitation is more enriched than that of groundwater. The main water source of C. scoparium and C. mongolicum was soil moisture. The utilization rate of 0-40 cm soil layer was 27% (C.scoparium) and 33% (C.mongolicum), and the utilization rate of 40-80 cm soil layer was 32% (C.scoparium) and 25% (C.mongolicum). The average proportional similarity index (PS index) between the two species was 95.67%, indicating a competitive relationship with water resources. When the surface layer (0-40) soil moisture is high (July, August), both species preferentially absorb water from this layer, and the water competition is reduced. The average PS index is 89%. When the surface layer (0-40) was deficient in soil moisture (June, September and October), the water competition increased, and the PS index was 97.83%. This study emphasized the adaptation strategies of these shrubs to arid environments and found that it provided key insights for optimizing vegetation density and species composition in desert aerial seeding areas and ensuring sustainable ecological restoration in the study area.